PERSUASI DALAM CERAMAH PENGAJIAN K.H. MUHAMMAD ZAINI ABDUL GHANI (PERSUASIVE IN ISLAMIC LECTURING KH. MUHAMMAD ZAINI ABDUL GHANI) - Maulida Yuniarti (JURNAL BAHASA, SASTRA DAN PEMBELAJARANNYA, 2023)
AbstractPersuasive In Islamic Lecturing KH. Muhammad Zaini Abdul Ghani. The purpose of this study was to describe the use of form and persuasion techniques used in KH's recitation lectures. Zaini Abdul Ghani. The method used in this research is descriptive with a qualitative approach. Data collection was carried out by interviewing the congregation and observing the recitation video. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The results showed that the lectures of KH. Zaini Abdul Ghani applies forms and techniques of persuasion. KH. Zaini Abdul Ghani tries to attract, hope, and move the congregation as an application of persuasion. In the technique of persuasion KH. Zaini Abdul Ghani applies rationalization, knowing, suggestion, conformity, compensation, replacement, and estimation. The findings that the researchers found, KH. Zaini Abdul Ghani attracted the attention of the congregation who were dominated by presenting materials related to new or sensational things, presented in a simple language style, and always inserting humor. In addition, KH. Zaini Abdul Ghani also attracted the attention of the congregation by associating the material with actual, diverse sentence structures, using Banjar proverb quotes to explain the recitation material, including comparisons and examples, asking questions to the congregation, connecting with local events and figures, and teaching descriptions of events that will be happening. happen in the future. KH. Zaini Abdul Ghani in the recitation tries to make the congregation by presenting the material that is included with specific and concrete examples. The example given by KH. Zaini Abdul Ghani was not only conveyed through recitation, but also exemplified his practice in everyday life. In addition, in an effort to realize the congregation, KH. Zaini Abdul Ghani quotes books, hadiths, and interpretations of the holy verses of the Qur'an. In an effort to touch and move the congregation, KH. Zaini Abdul Ghani by finding and selecting material discussions that suit the wishes and needs of the congregation. The persuasion technique used is by conveying the material rationally, trying to direct the congregation, giving advice, positioning themselves such as, directing the congregation to act in accordance with the teachings of the Prophet, the congregation to prioritize and multiply worship, as well as describing future ideals.Keywords: persuasion, lecture, recitation. KH. Zaini Abdul Ghani, IslamicAbstrakPersuasi dalam Ceramah Pengajian KH. Muhammad Zaini Abdul Ghani. Tujuan dari penelitian ini ialah untuk mendeskripsikan penggunaan wujud dan teknik persuasi yang digunakan dalam ceramah pengajian KH. Zaini Abdul Ghani. Metode yang digunakan dalam penelitian ini yaitu deskriptif dengan pendekatan kualitatif. Pengumpulan data dilakukan dengan wawancara jamaah dan observasi video pengajian. Teknik analisis data meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan ceramah pengajian KH. Zaini Abdul Ghani menerapkan wujud dan teknik persuasi. KH. Zaini Abdul Ghani berusaha untuk menarik, meyakinkan, dan menggerakkan jamaah sebagai penerapan wujud persuasi. Pada teknik persuasi KH. Zaini Abdul Ghani menerapkan rasionalisasi, identifikasi, sugesti, konformitas, kompensasi, penggantian, dan proyeksi. Temuan yang peneliti temukan, KH. Zaini Abdul Ghani menarik perhatian jamaah didominasi dengan cara memaparkan materi-materi terkait hal-hal baru atau fakta sensasional, disajikan dengan gaya bahasa yang sederhana, dan selalu menyelipkan humor. Selain itu, KH. Zaini Abdul Ghani juga menarik perhatian jamaah dengan mengaitkan materi dengan peristiwa aktual, struktur kalimat yang beragam, menggunakan kutipan Peribahasa Banjar untuk menjelaskan materi pengajian, menyertakan perbandingan dan contoh, mengajukan rangkaian pertanyaan kepada jamaah, menghubungkan dengan peristiwa dan tokoh lokal, dan mengajarkan gambaran peristiwa yang akan terjadi pada masa yang akan datang. KH. Zaini Abdul Ghani dalam pengajian berusaha untuk meyakinkan jamaah dengan cara memaparkan materi disertakan dengan contoh yang spesifik dan konkrit. Contoh yang diberikan KH. Zaini Abdul Ghani tak hanya disampaikan melalui pengajian, tetapi juga dicontohkan pengamalannya dalam kehidupan sehari-hari. Selain itu, dalam upaya untuk meyakinkan jamaah, KH. Zaini Abdul Ghani mengutip kitab, hadist, dan tafsir ayat suci Al-Qur’an.Sebagai upaya untuk menyentuh dan menggerakkan jamaah, KH. Zaini Abdul Ghani dengan cara menemukan dan memilih bahasan materi yang dikaitkan dengan keinginan dan kebutuhan jamaah. Teknik persuasi yang digunakan yakni dengan menyampaikan materi pengajian dengan rasional, berusaha mengaburkan konflik jamaah, memberikan nasihat, memposisikan diri seperti jamaah, mengarahkan jamaah untuk bertindak sesuai dengan ajaran Rasulullah, memotivasi jamaah untuk mengutamakan dan memperbanyak ibadah, serta memaparkan cita-cita untuk masa yang akan datang.Kata-kata kunci: persuasi, ceramah, pengajian. KH. Zaini Abdul Ghani, Islam